(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the article determined and analyzed the main motifs, linguistic images and symbolism of immigrant Lemkos songs. Attention is drawn to imagery language of songs and presence of dialecticism, that create local colour.